Khu vườn bí mật - Burnett, Frances Hodgson, 1849-1924 (Nhà xuá̂t bản Văn học, 2007)
Orphaned, ten-year-old Mary comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden.